2015
DOI: 10.1039/c5cs00108k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in automotive catalysis for NOx emission control by small-pore microporous materials

Abstract: The ever increasing demand to develop highly fuel efficient engines coincides with the need to minimize air pollution originating from the exhaust gases of internal combustion engines. Dramatically improved fuel efficiency can be achieved at air-to-fuel ratios much higher than stoichiometric. In the presence of oxygen in large excess, however, traditional three-way catalysts are unable to reduce NOx. Among the number of lean-NOx reduction technologies, selective catalytic reduction (SCR) of NOx by NH3 over Cu-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
772
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 794 publications
(796 citation statements)
references
References 175 publications
15
772
0
9
Order By: Relevance
“…Some researchers 16,17 argued that a mixture of Cu(I)-Cu(II) oxidation states will exist during standard SCR process, but it is not generally accepted yet. 4 Another interesting phenomenon is that fast SCR (equation 2) reacts more rapid than standard SCR (equation 1), of which the intrinsic reason is still under debate. Some studies 18,19 suggested that in fast SCR, NO and NO 2 would bind in gas phase to form N 2 O 3 , followed by a hydrolysis to nitrous acid (N 2 O 3 + H 2 O −−→ 2HONO).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers 16,17 argued that a mixture of Cu(I)-Cu(II) oxidation states will exist during standard SCR process, but it is not generally accepted yet. 4 Another interesting phenomenon is that fast SCR (equation 2) reacts more rapid than standard SCR (equation 1), of which the intrinsic reason is still under debate. Some studies 18,19 suggested that in fast SCR, NO and NO 2 would bind in gas phase to form N 2 O 3 , followed by a hydrolysis to nitrous acid (N 2 O 3 + H 2 O −−→ 2HONO).…”
Section: Introductionmentioning
confidence: 99%
“…Among zeolites, a majority of studies in past decade were conducted on copper exchanged small-pore CHAtype zeolites (Cu-SAPO-34 and Cu-SSZ-13) because of their high NO x conversion as well as N 2 selectivity, non-toxicity, wider operation temperature range, and excellent hydrothermal stability in diesel engines. [2][3][4]9 Owing to the uniqueness of zeolite structure, the reaction mechanism of NH 3 -SCR differs a lot between zeolites and traditional catalysts. For example, there are two kinds of possible active sites in Cu exchanged CHA-type zeolites: the Brønsted acid (H in the zeolite framework) and Lewis acid (introduced Cu ion) site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] Commercially,one of the most important zeolites is ZSM-5 with MFI framework topology,w hich has become ubiquitous in petroleum refining and chemical manufacturing.…”
mentioning
confidence: 99%
“…[3,4] Commercially,one of the most important zeolites is ZSM-5 with MFI framework topology,w hich has become ubiquitous in petroleum refining and chemical manufacturing. [2] Thee normous quantities at which this material is utilized at the global scale continue to drive research targeting improved performance.…”
mentioning
confidence: 99%